Adobe Acrobat X PDF bible - Padova, Ted (Bible., 2011)
The classic Acrobat and PDF reference, updated to cover the latest release Consistently the most authoritative and comprehensive resource on the Acrobat PDF format, this standard reference returns with in-depth coverage of the newest version of Acrobat. Written by bestselling author Ted Padova, this book is packed with real-world insights and techniques gained from Padova's daily use of Acrobat under deadline constraints. You'll discover everything there is to know about using Acrobat X for print prepress, the Internet, CD-ROMs, and other forms of media. Popular author Ted Pado.